Efficient carry select 16-bit square root adder with complementary metal-oxide semiconductor implementation - Pavitha Uppinakere Sathyanarayan; Mamtha Mohan; Sandeep Kakde; Annam Karthik (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
The adder is the maximum usually used mathematics block in programs inclusive of central processing unit (CPU) and virtual sign processing. As a result, it is important to expand a space-saving, low-strength, high-overall performance adder circuit. The hassle is diagnosed to layout mathematics sub structures with minimized strength dissipation, low area, and minimal time postpone of common-sense circuits. In conventional carry select adder (CSA), the time required to generate the sum output is less than other basic adder circuits but the principal difficulty is the location because the variety of transistors used to put in force the CSA circuit is fairly more. So, the area increases because of which the overall power consumption of the circuit will be more. If it's far viable to lessen the variety of transistors used withinside the structure of CSA adder, then, the strength intake of the circuit may be decreased or even the reaction time will improve. By lowering the area of the adder circuit, the suggested solution intends to reduce power consumption and latency.